Graphene‐Based Intrinsically Stretchable 2D‐Contact Electrodes for Highly Efficient Organic Light‐Emitting Diodes. Issue 31 (1st July 2022) - Zhou, Huanyu; Han, Shin Jung; Harit, Amit Kumar; Kim, Dong Hyun; Kim, Dae Yoon; Choi, Yong Seok; Kwon, Hyeokjun; Kim, Kwan‐Nyeong; Go, Gyeong‐Tak; Yun, Hyung Joong; Hong, Byung Hee; Suh, Min Chul; et al.
Abstract: Intrinsically stretchable organic light‐emitting diodes (ISOLEDs) are becoming essential components of wearable electronics. However, the efficiencies of ISOLEDs have been highly inferior compared with their rigid counterparts, which is due to the lack of ideal stretchable electrode materials that can overcome the poor charge injection at 1D metallic nanowire/organic interfaces. Herein, highly efficient ISOLEDs that use graphene‐based 2D‐contact stretchable electrodes (TCSEs) that incorporate a graphene layer on top of embedded metallic nanowires are demonstrated. The graphene layer modifies the work function, promotes charge spreading, and impedes inward diffusion of oxygen and moisture. The work function (WF) of 3.57 eV is achieved by forming a strong interfacial dipole after deposition of a newly designed conjugated polyelectrolyte with crown ether and anionic sulfonate groups on TCSE; this is the lowest value ever reported among ISOLEDs, which overcomes the existing problem of very poor electron injection in ISOLEDs. Subsequent pressure‐controlled lamination yields a highly efficient fluorescent ISOLED with an unprecedently high current efficiency of 20.3 cd A −1, which even exceeds that of an otherwise‐identical rigid counterpart. Lastly, a 3 inch five‐by‐five passive matrix ISOLED is demonstrated using convex stretching. This work can provide a rational protocol for designing intrinsically stretchable high‐efficiency optoelectronic devices with favorable interfacial electronic structures. Abstract : A protocol to fabricate highly efficient organic light‐emitting diodes that use an intrinsically stretchable 2D‐contact electrode topped with graphene is reported. As a benefit of the fast carrier mobility with complete 2D contact with the organic material and the tunable work function of the 2D‐contact stretchable electro (TCSE), the limited charge injection of the widely used silver‐nanowire‐based stretchable electrode is solved.